Cartagena de Indias and the Colombian Caribbean : Territorial intelligence and possible territories. The OIDTe, tools for sustainable transformation - Alfonso, Rodríguez Linares (2010)
Fil: Bozzano, Horacio. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación. Instituto de Investigaciones en Humanidades y Ciencias Sociales (UNLP-CONICET); Argentina.